2020
DOI: 10.3390/ijerph17134693
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Forecasting the COVID-19 Temporal Spread in Greece: An Exploratory Approach Based on Complex Network Defined Splines

Abstract: Within the complex framework of anti-COVID-19 health management, where the criteria of diagnostic testing, the availability of public-health resources and services, and the applied anti-COVID-19 policies vary between countries, the reliability and accuracy in the modeling of temporal spread can prove to be effective in the worldwide fight against the disease. This paper applies an exploratory time-series analysis to the evolution of the disease in Greece, which currently suggests a success story of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 40 publications
(121 reference statements)
0
62
0
4
Order By: Relevance
“…To end the debate on whether or not climatic conditions can play an independent role-and, if so, to what extent-as a key modulating factor in COVID-19 onset and transmission [18,31,39], a number of other factors must be considered [24,40,41] in scenarios of not only high complexity, but also significant uncertainty, as mentioned at the beginning of this paper. The available number of cases and especially deaths in the total population are also influenced by the following factors: (i) the early detection of the pathogen; (ii) the number of investigations carried out, their statistical assessment, and possible under/overestimations [13,42,43]; (iii) demography in terms of population age and density [44,45]; (iv) urban texture, mobility, and social habits of the population [46,47]; (v) restrictions by local and national governments, such as quarantine and lockdown [35,48]; and (vi) medical care and susceptibility of the hosts [49][50][51]. These factors are almost entirely unrelated to h. On this topic, even in spite of possible correlations between some variables, the recent literature [52] has suggested that confounding factors, including some climatic ones [53][54][55][56][57], are nearly ready to be satisfactorily weighed.…”
Section: Discussionmentioning
confidence: 99%
“…To end the debate on whether or not climatic conditions can play an independent role-and, if so, to what extent-as a key modulating factor in COVID-19 onset and transmission [18,31,39], a number of other factors must be considered [24,40,41] in scenarios of not only high complexity, but also significant uncertainty, as mentioned at the beginning of this paper. The available number of cases and especially deaths in the total population are also influenced by the following factors: (i) the early detection of the pathogen; (ii) the number of investigations carried out, their statistical assessment, and possible under/overestimations [13,42,43]; (iii) demography in terms of population age and density [44,45]; (iv) urban texture, mobility, and social habits of the population [46,47]; (v) restrictions by local and national governments, such as quarantine and lockdown [35,48]; and (vi) medical care and susceptibility of the hosts [49][50][51]. These factors are almost entirely unrelated to h. On this topic, even in spite of possible correlations between some variables, the recent literature [52] has suggested that confounding factors, including some climatic ones [53][54][55][56][57], are nearly ready to be satisfactorily weighed.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, besides self-organizing models, a variety of numerous other modeling (lattice model, network model, mathematical model, etc.) approaches regarding COVID-19 epidemics have been developed [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; among these, the compartmental SIR (Susceptible, Infectious, or Recovered) models exhibit very interesting results, which are discussed below in Section 4 .…”
Section: Introductionmentioning
confidence: 99%
“…To end the debate on whether or not climatic conditions can play an independent role -and if so, to what extent -in COVID-19 onset and transmission [18,38], a number of other factors must be considered [24,39,40] in scenarios of not only high complexity but also significant uncertainty, as mentioned at the beginning of this paper. The available number of cases, and especially deaths, in the total population are also influenced by the following factors: i) the number of investigations carried out, their statistical assessment, and possible under/overestimations [13,41,42]; ii) demography in terms of population age and density [43,44]; iii) urban texture, mobility, and social habits of the population [45,46]; iv) restrictions by local and national governments, such as quarantine and lockdown [34,47]; and v) medical care and susceptibility of the hosts [48][49][50]. These factors are almost entirely unrelated to h. On this topic, the recent literature [51] has suggested that confounding factors, including some climatic ones [52,56], are nearly ready to be satisfactorily weighed.…”
Section: Discussionmentioning
confidence: 99%